PEDAGOGICAL AND PSYCHOLOGICAL FOUNDATIONS OF MODELING LANGUAGE TEACHING IN THE EDUCATIONAL PROCESS OF GENERAL SECONDARY SCHOOLS (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the pedagogical and psychological foundations of modeling language teaching in the educational process of general secondary schools. The theoretical and practical aspects of using modeling technologies are highlighted, and their role in developing students’ communicative competence is demonstrated. As pedagogical foundations, the systematization of the educational process, the visual representation of knowledge, and methodological effectiveness are emphasized. The psychological foundations are aimed at activating students’ cognitive activity, increasing their motivation, and developing their thinking processes. The results of the article indicate the necessity of widely implementing innovative approaches in language education.
Keywords: Language teaching, modeling, pedagogical foundations, psychological foundations, general secondary education, communicative competence, educational technologies.